Comparison of Segger and Other Methods for Segmentation and Rigid-Body Docking of Molecular Components in Cryo-EM Density Maps - Pintilie, Grigore (2012)
Segmentation and docking are useful methods for discovery of molecular components in cryo-EM (Electron Cryo-Microscopy) density maps of macromolecular complexes. In this paper, we describe the segmentation and docking methods implemented in Segger. For 12 targets included in the 2010 Cryo-EM Modeling Challenge, we segmented the regions corresponding to individual molecular components using Segger. We then used the segmented regions to guide rigid-body docking of individual components. An assessment in the accuracy of the component segmentation of the targets based on Segger and other methods was made by comparing the docking results of individual components to the segmented regions. The docking results were evaluated by comparison to published structures and by calculation of several scores including atom inclusion, density occupancy, and geometry clash.